PERAN KPU DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PEMILIHAN KEPALA DAERAH DI KALIMANTAN TIMUR - Idris, Fahmi (Journal of Law ( Jurnal Ilmu Hukum ), 2025)
ABSTRACTThe role of the KPU in increasing public participation is closely related to transparency and accountability in the implementation of the regional elections. Public trust in the election process is greatly influenced by the extent to which the KPU is able to hold elections that are free from fraud, manipulation, and political intervention. The level of voter participation is also influenced by the effectiveness of campaigns and socialization carried out by regional head candidates. This research will answer the legal provisions that regulate the role of the KPU in increasing public participation in the election of regional heads in East Kalimantan and the legal factors that support and hinder the KPU's efforts to increase public participation in the election of regional heads in East Kalimantan. Using normative legal research as literature law research by using various literature as research materials and analysis materials. The results of the discussion and research are that the KPU plays a very important role in the implementation of the Regional Elections, especially in increasing public participation. Based on existing legal provisions, the KPU has the obligation to hold participatory, transparent, and fair elections. The KPU needs to strengthen socialization and voter education, especially in remote areas, to increase public understanding of the importance of the Regional Elections. In addition, there needs to be further efforts to improve election infrastructure in hard-to-reach areas and tackle the practice of money politics through stricter supervision. Keywords: General Election Commission, Regional Head Election, Community Participation.